Proteomic analysis of seminal plasma in Bali-polled bulls: Identifying biomarkers for fertility assessment (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aimed to conduct a proteomic analysis of the seminal plasma using advanced proteomic techniques in Bali-polled bulls in order to assess fertility. Materials and Methods: Semen samples from Bali-polled bulls (n = 5) were analyzed via one-dimensional sodium dodecyl sulfate-polyacrylamide gel electrophoresis for protein separation, followed by liquid chromatography–mass spectrometry for peptide identification. Data were processed using the UniProt bovine protein database and STRING software. Result: A total of 84 proteins were identified, with two remaining unclassified. These proteins were categorized into key biological processes, including reproduction, regulation of biological quality, and catabolic processes. Molecular functions predominantly included catalytic activity, hydrolase activity, and peptidase regulator activity, while cellular components were primarily associated with the extracellular region, vesicles, and lysosomes. Thirteen proteins were identified as directly linked to fertility functions: SPADH1, Binder of Sperm Proteins 3, SPADH2, ANG, Binder of Sperm Proteins 5, TEX101, ELSPBP1, FOLR3, TCP1, LDHC, HEXA, SPAM1, and CTSB. These proteins were further analyzed for their functional relevance to reproductive biology. Conclusion: While these findings provide preliminary insights into fertility-related biomarkers for Bali-polled bulls, further validation and statistical analysis are required to confirm their diagnostic and breeding potential. This proteomic analysis represents a first step toward understanding the molecular mechanisms of fertility in this underrepresented breed, contributing to improved breeding strategies and genetic resource management. Future studies should aim to expand the sample size, validate the identified biomarkers through experimental assays, and explore their potential for broader applications in bovine fertility management.J. Adv. Vet. Anim. Res., 12(3): 698–708, September 2025http://doi.org/10.5455/javar.2025.l933